Global sliding mode control integrated with extended state observer for wheel slip tracking - Đàm Hữu Mạnh; Nguyễn Xuân Nam; Phạm Xuân Đức; Nguyễn Thế Anh; Lê Đức Thịnh; Nguyễn Tùng Lâm (Journal of Military Science and Technology, 2024)
The Anti-lock Braking System (ABS) is crucial for vehicle safety by maintaining wheel traction during braking and preventing wheel lock-up. This study proposes an advanced Global Sliding Mode Control (GSMC) strategy to enhance ABS performance. The nonlinear global sliding mode of the surface is designed based on the exponential approach law. The method can eliminate the reaching phase compared with Sliding Mode Control (SMC), and guarantee the system robustness during the whole control process. The Extended state observer (ESO) is used in combination with the design of the GSMC in order to estimate the total uncertainty in the system. Simulation results demonstrate that the proposed global sliding mode control scheme enables the wheel slip-ratio to converge to optimal value quickly with the small oscillation, and has a relatively short braking distance and braking time, which is very suitable to prevent the wheel from being locked during braking.